Division, Persecution and Rearrangement - The AKP’s Controversial Relationship with Turkish Civil Society - Turkmen, Seref (European Scientific Journal, ESJ, 2023)
Turkish culture has always valued foundations, such as mosques, schools, public baths, free kitchens, and hospitals. However, much of this structure was abolished by Mustafa Kemal Ataturk after the proclamation of the republic in 1923. Turkish civil society was slowly reorganized following Western examples and had a second heyday under Turgut Ozal’s liberal economic policy and media market liberalization. However, after the Justice and Development Party came to power in 2002, civil society in Turkey was significantly rearranged. This article discusses the conflicts and current situation of Turkish civil society, including the campaign against Amnesty International and the Open Society Foundation. Sources include renowned Turkish journalists and abundant literature in Turkish and English.